Pengetahuan tentang Manajemen Laktasi pada Ibu Menyusui Mendukung Keberhasilan ASI Eksklusif - Reni Ulfa Lailatul Magfiroh; Endah Kusuma Wardani; Desy Purnamasari (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Promoting breastfeeding is one of the objectives to be attained under the Sustainable Development Goals (SDGs) policy. Coverage of breastfeeding, both globally and regionally, still needs to meet standards, and one of the elements that can impact breastfeeding success is the extent of the mother's knowledge about lactation management. This study aimed to analyze the correlation between the level of knowledge about lactation management and exclusive breastfeeding in breastfeeding mothers. This study was designed as an observational analytic research utilizing a cross-sectional approach. The sample comprised 51 individuals, selected using random sampling technique that fulfilled the predetermined criteria for inclusion (breastfeeding mothers aged 6-12 months) and exclusion criteria (mothers with comorbidities). This study was conducted in the working area of the Tulungrejo Community Health Center in December 2023. To assess the mother's understanding of lactation management, a questionnaire was utilized as the research instrument. The chi-square test with the assistance of the SPSS 25 software was applied to analyze the data. The results indicated that 45.1% of mothers had sufficient knowledge, and 52.9% did not breastfeed exclusively. Statistical test results p value 0.000 < 0.05 indicated a correlation between between the knowledge level of lactation management and exclusive breastfeeding. The expectation is for health workers and breastfeeding support groups to play a significant role in educating mothers about lactation management during pregnancy, which is carried out consistently so that mothers can provide breast milk exclusively to babies.